Indicadores bioquímicos séricos e do líquido peritoneal de equinos submetidos à obstrução intestinal - Di Filippo, Paula Alessandra; Alves, Aracele Elisane [UNESP]; Hermeto, Larissa Correia [UNESP]; Santana, Aureo Evangelista [UNESP] (FapUNIFESP (SciELO), 2012)
Twenty-four horses were distributed into four different groups, instrumented control (GI), duodenum obstruction (GII), ileum obstruction (GIII) and large colon obstruction (GIV). Serum and peritoneal fluid analysis of aspartate aminotransferase, creatine kinase, lactate dehydrogenase, alkaline phosphatase, inorganic phosphorus and lactate were measured. Samples were collected one hour before the surgical procedure (T0); 3 hours after the obstruction (T3ob), 1, 3, 12, 24, 120 and 168 hours after the beginning of reperfusion/deobstruction. Duodenal (GII) and ileum (GIII) obstructions changed serum and peritoneal fluid biochemical analysis. However, only lactate, lactate dehydrogenase, creatine kinase and inorganic phosphorus concentrations were abnormal in peritoneal fluid three hours after the obstruction. The biochemical analysis of peritoneal fluid allowed a faster diagnostic of intestinal alterations than the serum analysis; hence it should be prioritized when pre-operatory colic assessment is carried out.
Serum and peritoneal fluid biochemical markers of horses: Submitted to intestinal obstruction
Keywords: Biomarkers; Colic; Equine; Equidae